STUDY ON FACTORS ASSOCIATED WITH CHRONIC PAIN IN ELDERLY PATIENTS (Tạp chí Y học Cộng đồng, 2026)
Objectives: To identify factors associated with chronic pain among elderly patients.Subjects and methods: A cross-sectional descriptive study was conducted on 240 patients aged 60 and older, diagnosed with chronic pain according to the International Association for the Study of Pain (IASP) criteria, and treated at Military Medical Hospital 103 from August 2025 to April 2026.Results: The mean age of the study participants was 70.47 ± 6.72 years. The mean pain intensity was 6.22 ± 1.48/10 points, with most patients experiencing moderate pain (50.83%) or severe pain (44.58%). Factors associated with severe chronic pain included pain located in the trunk region (67.86%, p
Keywords: Chronic pain; elderly patients; Visual Analog Scale (VAS).